Desain Ruang Kerja Unit Kerja Rekam Medis Rumah Sakit X Berdasarkan Aspek K3 - Suyoso, Gandu Eko Julianto; Alfiansyah, Gamasiano; Hastri, Encik Ameilia Permata (Puslitbang Sinergis Asa Professional, 2023)
Hospital X does not yet have an ideal medical records unit workspace. Medical record personnel have complained of localized fatigue in the back and shoulders. This study is qualitative in nature. The aim of this research is to redesign the medical records unit workspace at Hospital X in accordance with health and safety standards, especially ergonomic and physical aspects. Data collection was conducted through interviews, observations, and measurements. The research results indicate a mismatch in the dimensions of chairs and work desks with the anthropometrics of the personnel. The redesigned medical records unit workspace has dimensions of 7.33 meters x 3 meters and includes passive ventilation with a window area of 3.3 m2. Recommendations from this study suggest that the hospital should consider the compatibility of work furniture with the anthropometrics of its workers, given that ergonomic aspects can lead to work fatigue.